2019
DOI: 10.1097/adm.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Brief Intervention, and Referral to Treatment for Prenatal Alcohol Use and Cigarette Smoking: A Survey of Academic and Community Health Care Providers

Abstract: Objectives: Prenatal alcohol and cigarette smoking are associated with numerous adverse pregnancy outcomes. Screening, Brief Intervention, and Referral to Treatment (SBIRT) represents a standardized approach; however, implementation in routine pregnancy care remains a challenge. The purpose of the study was to determine current practices, barriers to implementation, and education needs of healthcare providers utilizing SBIRT to address prenatal alcohol and cigarette smoking. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
(22 reference statements)
3
15
0
1
Order By: Relevance
“…Additionally, using screening tools that can assess a broad spectrum of alcohol use problems (ie, mild to severe) can lead to more opportunities for clinicians to conduct appropriate brief interventions or provide referrals to treatment of the patient. A 2020 cross-sectional study surveyed family physicians, midwives, and obstetricians practicing in Canada and found that although nearly all clinicians reported screening pregnant women for alcohol use, brief interventions were not conducted as widely ( 32 ), which is consistent with the results of our analysis. USPSTF recommends that a brief intervention lasts 6 to 15 minutes and facilitates tailored feedback about the patient’s risks and potential consequences of their current drinking habits ( 23 , 33 ).…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, using screening tools that can assess a broad spectrum of alcohol use problems (ie, mild to severe) can lead to more opportunities for clinicians to conduct appropriate brief interventions or provide referrals to treatment of the patient. A 2020 cross-sectional study surveyed family physicians, midwives, and obstetricians practicing in Canada and found that although nearly all clinicians reported screening pregnant women for alcohol use, brief interventions were not conducted as widely ( 32 ), which is consistent with the results of our analysis. USPSTF recommends that a brief intervention lasts 6 to 15 minutes and facilitates tailored feedback about the patient’s risks and potential consequences of their current drinking habits ( 23 , 33 ).…”
Section: Discussionsupporting
confidence: 83%
“…A survey of midwives from East of England showed that 60% routinely enquired about alcohol but only 29% routinely provided alcohol advice (Winstone & Verity, 2015). Similar findings were reported in a study of 118 healthcare professionals including midwives carried out in Canada (Ordean et al, 2020). Despite other studies in Norway, Australia and England reporting almost all midwives ask about alcohol and advise abstinence in line with the guidelines; fewer do so after the initial booking appointment and many do not use a validated alcohol screening tool to do so (Schölin et al, 2021; Smith, Dyson, et al, 2021).…”
Section: Introductionsupporting
confidence: 90%
“…Technology provides an exciting option. It can be implemented consistently across patients, with minimal staff involvement, and conducted during natural waiting periods, integrating easily within the workflow of the clinic [ 17 - 19 ]. It has also been shown to improve disclosure of substance use in anonymous studies [ 20 ].…”
Section: Introductionmentioning
confidence: 99%